Measuring the Relationship between Behavioral Intention and Customer-based Brand Equity by Using the Structural Equation Model - Hoang, Thu Huong (ĐHKT, 2016)
Based on the Structural Equation Model method, this paper expresses how to examine the relationship among tourists behavioral intention and destination brand equity. The definition of customer-based destination brand equity is a combination of key factors, which are measured by four components, destination brand image, destination brand awareness, destination brand quality, and destination brand loyalty.